Pediatric radiology - Reid, Janet; Lee, Edward; Paladin, Angelisa; Carrico, Caroline; Davros, William ([New York] : Oxford University Press, 2014)
Constructed of concise, topically focused chapters that offer a quick review of clinical problems, this resource provides a comprehensive review of 120 pathologies commonly encountered by practising radiologists and residents. It offers a guided approach to imaging diagnosis with a constant depth of coverage, a structured template, and incorporation of applied physics. A definition is given for each pathology, followed by: demographics, clinical presentation, imaging modalities and features, imaging algorithm, applied physics, differential diagnoses and pitfalls, and a bulleted summary of key points.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on February 10, 2014).
Keywords: Pediatric radiology